SKRINING GEN GLUKOSILTRANSFERASE (GTF) DARI BAKTERI ASAM LAKTAT PENGHASIL EKSOPOLISAKARIDA - Malik, Malik; Ariestanti, Donna M; Nurfachtiyani, Anandayu; Yanuar, Arry (UI Scholars Hub, 2018)
Screening for glucosyltransferase gene (gtf) from exopolysaccahride producing lactic acid bacteria. Glucosyltransferase (GTF) is an enzyme involved in exopolysaccharide (EPS) polymer synthesis in microbes. One example of EPS that has been used in pharmaceutical and medical application is dextran. Dextran has been used in conjugated-drug delivery system as matrix. As a group of microbes producing EPS, lactic acid bacteria (LAB) have been well reported carrying sucrase genes glucosyltransferase (gtf), as well as fructosyltransferases (ftf). In an attempt to search for novel gtf genes as the aim of this study, LAB collection isolated from local sources yielded from previous study were screened performing PCR using degenerate primers DegFor and DegRev. An approximately 660 base pairs (bp) amplicons were obtained by using genomic DNAs of those LAB isolates as templates with conserved region of gtf genes catalytic domain as target. Two out of 20 LAB strains were yielded no amplicon as observed on agarose gel, while one strain exhibited non-specific amplicon DNA bands with sizes other than 660 bp. The two negative ones were isolated from soil obtained from dairy product waste field and from waste of soy sauce from previous study, while the latter was isolated from waste of soy sauce.